2020
DOI: 10.1002/ente.202000056
|View full text |Cite
|
Sign up to set email alerts
|

Micro versus Nano: Impact of Particle Size on the Flow Characteristics of Silicon Anode Slurries

Abstract: Silicon is interesting for use as a negative electrode material in Li‐ion batteries due to its extremely high gravimetric capacity compared with today's state‐of‐the‐art material, graphite. However, during cycling the Si particles suffer from large volume changes, leading to particle cracking, electrolyte decompositions, and electrode disintegration. Although utilizing nm‐sized particles can mitigate some of these issues, it would instead be more cost‐effective to incorporate μm‐sized silicon particles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Indeed, several groups have focused their research on obtaining innovative Si nano-structures to limit the difficulties associated with the volumetric expansion [75,76]. Nevertheless, incorporating micron-sized particles is unequivocally more cost-effective for processing real Li-ion anodes [77]. Furthermore, Si requires fluoroethylene carbonate (FEC) as an additive in the electrolyte to form a stable SEI, which further increases the cost of the cell [71,78].…”
Section: Conversion/alloying Materials Silicon (Si)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several groups have focused their research on obtaining innovative Si nano-structures to limit the difficulties associated with the volumetric expansion [75,76]. Nevertheless, incorporating micron-sized particles is unequivocally more cost-effective for processing real Li-ion anodes [77]. Furthermore, Si requires fluoroethylene carbonate (FEC) as an additive in the electrolyte to form a stable SEI, which further increases the cost of the cell [71,78].…”
Section: Conversion/alloying Materials Silicon (Si)mentioning
confidence: 99%
“…Some more realistic research fields attempting the adoption of Si as a regular anode material have been associated with the development of novel binders to minimise the impact of the volumetric expansion [69,79] or the prelithiation of Si-based electrodes to mitigate the capacity losses during the first cycles [75,80,81]. In any case, Si is usually added as an additive, blended with graphite, in the anode formulation [75,77,81] as the aforementioned difficulties associated with its volume change limit its use as the sole active material. In the last years, the development of Si-carbon composites has been widely promoted due to the industrial interest of Si [82][83][84][85].…”
Section: Conversion/alloying Materials Silicon (Si)mentioning
confidence: 99%
“…Of course, the rheological properties of the slurry without Si nanoparticles must not necessarily have to be similar to the ones of a slurry containing a small addition of Si nanoparticles. In fact, evidence suggests that the rheological properties of graphite/Si slurries differ when using μm-sized and nm-sized Si particles [56]. However, Si in dried electrodes is visible by common microscopy techniques such as Scanning Electron Microscopy (SEM), which allows reproducing its location ad hoc without the need of following their particle evolution from the slurry to the dried electrode.…”
Section: Generation Of the Microstructural Modelmentioning
confidence: 99%
“…14 The Si size influence has been studied in the slurry rheology with 35% solid content, revealing a higher viscosity for Si nanoparticle-graphite blends (Si Nps/Gr) than Si microparticle-graphite blends (Si µps/Gr). 15 Another helpful technique is to perform frequency sweeps, where the storage (G') and loss (G") modulus can provide hints about the slurry stability and microstructure. However, these slurry studies are reported less frequently.…”
Section: Introductionmentioning
confidence: 99%